A multi-angle analysis of injury induced by supplementation of soybean meal in Litopenaeus vannamei diets - Peng, Kai; Qiu, Jianqiang; Li, Chaozheng; Lu, Huijie; Liu, Zhenxing; Liu, Ding; Huang, Wen (Frontiers in Microbiomes, 2023)
Soybean meal is considered as one of the major components of Litopenaeus vannamei diets. However, most previous studies have focused on evaluating the effects of soybean meal on L. vannamei from the perspective of growth, physiology, and feed utilization; information regarding the analysis of serum metabolites, antioxidant and immune response, and intestinal microbiota is limited. Five diets were prepared, comprising 20% (T20), 28% (T28), 35% (T35), 42% (T42), and 50% (T50) soybean meal. A total of 600 shrimp were randomly distributed into 20 tanks (i.e., 30 shrimp per tank), with four tanks assigned to each dietary group. Shrimp were fed to apparent satiation during the 42-day feeding trial. The results showed that levels of serum globulin, alanine aminotransferase, and aspartate aminotransferase linearly increased (p < 0.01), but levels of high-density lipoprotein cholesterol linearly decreased (p < 0.001) as the proportion of soybean meal in the diet increased. Supplementation of shrimp diets with soybean meal linearly and quadratically increased (p < 0.05) serum total antioxidant capacity, levels of malondialdehyde, and activities of catalase, nitric oxide synthase and phenoloxidase. Hepatocytes in T35, T42, and T50 were shown to have different degrees of vacuolar degeneration, hepatic corpuscle atrophy, and star-like lumen loss. Dietary inclusion of soybean meal altered the composition of intestinal bacterial microbiota at phylum level, especially increasing the abundance of on other bacterial genera, whereas it had minimal impact on other bacterial genera and had no significant influence on the bacterial diversity. This study suggests that dietary supplementation of L. vannamei diets with soybean meal at concentrations exceeding 28% induces inflammation and oxidant damage of the hepatopancreas, and increases the risk of intestinal disease.